Upaya Meningkatkan Kemampuan Menulis Puisi Menggunakan Metode Akrostik (Penelitian Tindakan Kelas) - Suherman, Achmad (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2022)
This study aims to see the extent to which students' ability to write poetry using the acrostic method. This has a very important role in improving the ability to write poetry that has been traditionally taught. The procedure carried out in this research is classroom action research through descriptive analysis, by finding the average value of the classical activity score and the percentage of learning outcomes. While the quantitative analysis is used to analyze the value of the subject's learning outcomes. The instruments used in the research were observation sheets and tests. The learning process with this acrostic method emphasizes the context of understanding student analysis, but can also be used by emphasizing psychological aspects. The subjects in this study were 30 people with 14 male students and 16 female students. In this study, the lecturer made improvements to learning in Indonesian subjects about writing poetry through the acrostic method. Based on the results of the research conducted, there were several improvements in learning to write poetry with the acrostic method, namely 36.7% in the first cycle to 63.3% in the second cycle of the total number of students as many as 30 people and the level of equity of understanding also increased to 56.3%. That is, there has been a significant improvement in the acrostic method. Then, some of the improvement of students' abilities with the application of the acrostic method, as follows: 1) students are more critical in analyzing the images presented, 2) students are more aware of the application of the material in the form of examples of images presented, and 3) students are more daring to speak in expressing their opinions.